2019
DOI: 10.3390/met9121249
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Compaction Pressure and Sintering Temperature on the Mechanical Properties of Porous Titanium for Biomedical Applications

Abstract: In the present work, the use of porous titanium is proposed as a solution to the difference in stiffness between the implant and bone tissue, avoiding the bone resorption. Conventional powder metallurgical technique is an industrially established route for fabrication of this type of material. The results are discussed in terms of the influence of compaction pressure and sintering temperature on the porosity (volumetric fraction, size, and morphology) and the quality of the sintering necks. A very good agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
2
6
1
Order By: Relevance
“…Considering the advantages and disadvantages of the experimental techniques to evaluate the Young's modulus of porous material, in this work, it has been evaluated following the two methods above mentioned (uniaxial compression test and ultrasounds technique), obtaining a higher value by ultrasounds than compression test (35 GPa vs 19 GPa, respectively). It has been previously reported by some of authors of this work [33,34,37,38] that there is a discrepancy between the value obtained by applying both experimental techniques. In Ni-Ti materials, this difference in the measured values is related to a super-elastic deformation within the linear-elastic range; it has been observed that, by the ultrasound technique, stiffness decreases for higher porosity values, according to the elastic Eshelby-based theory for closed, spherical porosity [39].…”
Section: Mechanical Behavior Of Porous Titanium Cylinderscontrasting
confidence: 58%
“…Considering the advantages and disadvantages of the experimental techniques to evaluate the Young's modulus of porous material, in this work, it has been evaluated following the two methods above mentioned (uniaxial compression test and ultrasounds technique), obtaining a higher value by ultrasounds than compression test (35 GPa vs 19 GPa, respectively). It has been previously reported by some of authors of this work [33,34,37,38] that there is a discrepancy between the value obtained by applying both experimental techniques. In Ni-Ti materials, this difference in the measured values is related to a super-elastic deformation within the linear-elastic range; it has been observed that, by the ultrasound technique, stiffness decreases for higher porosity values, according to the elastic Eshelby-based theory for closed, spherical porosity [39].…”
Section: Mechanical Behavior Of Porous Titanium Cylinderscontrasting
confidence: 58%
“…It is observed that pores of the specimens produced with uniaxial press method have a spherical morphology and shrink with the increase of compression pressure. The compression pressure applied to the powder material enables the small irregular pores to combine and hence lead to a reduction of the large-sized pores (Amidon et al, 2017;Castillo et al, 2019). It is seen that the pores of specimens fabricated by 3D printer are non-uniform and exist in different sizes.…”
Section: Density and Porositymentioning
confidence: 99%
“…It is seen that the pores of specimens fabricated by 3D printer are non-uniform and exist in different sizes. In the Binder Jetting method, pores are non-uniform due to the lack of compression pressure, the droplet effect of the liquid binder and, the accumulation of binder between particles (Kunchala and Kappagantula, 2018;Stevens et al, 2018;Castillo et al, 2019).…”
Section: Density and Porositymentioning
confidence: 99%
See 2 more Smart Citations